PEMIKIRAN PENDIDIKAN ISLAM ISMAIL RAJI AL-FARUQI - ., Norlaila (Pascasarjana UIN ANTASARI Banjarmasin, 2008)
Al-Faruqi is a very productive contemporary educational thinker and a Moslem scholar who has western educational background. I-Iowever, his thought still relbrs to Islamic teaching norms, Tauhid.. FIis view about fauhid is the basis for his thought and deed. In his concept, men are naturally bom with the potential to receive education. And through education men are going to be able to be the khalifatullah on the earth. In addition, he proposed Islamization of knowledge so that knowledge would refer and fruitful according to the essence of Tauhid. About curriculum, al-Faruqi suggests to implant Islamic teaching norm through lslamic cultural study. Then, for educational institution, he highlights the excellence of an institution called Tabyin and usrsh which were promoted by Hasan al-Bana for transmitting knowledge and transformation Islamic teaching lom generation to the next generation.